Edge Detection Technique Analysis to Determine Deformation In Bridge Structure - Sunarko Sunarko (Budapest International Research and Critics University, 2022)
Transportation infrastructure is one of the keys to economic development in Indonesia. As a result of the lack of addressing maintenance requirements and rehabilitation, bridge management systems are developed to help plan bridge maintenance and rehabilitation and to avoid a crisis reaction approach to maintain transportation infrastructure. However, the costs associated with developing and maintaining transport infrastructure in Indonesia continue to rise, and funding continues to shrink. Many evaluation methods are designed to operate on existing bridges without impairing their usefulness. Some of these methods are known as nondestructive evaluation (NDE) methods. Four imaging edge detection algorithms were selected for comparison in this paper: Fast Haar Transform (FHT), Fast Fourier Transform (FFT), Sobel, and Canny. This algorithm is used in many edge detection problems and considered here as a possible crack detection technique for bridge inspection problems.